2013
DOI: 10.1177/0049475513491943
|View full text |Cite
|
Sign up to set email alerts
|

HIV among the elderly with special reference to mode of presentation at a tertiary care hospital in Kolkata, India

Abstract: Epidemiological data of HIV affected individuals of aged 50 years and above in India are lacking for various reasons. Diagnosing HIV infection among the elderly is challenging as chronic HIV/AIDS can mimic those typically associated with aging in parallel to the myth that elderly individuals lead asexual lives. In this study, low-literate, poor, urban men were the major group. The most common presentation at diagnosis was frailty or unexpected weight loss and neurocognitive impairment, whereas the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…For instance, analyses of the Multicenter AIDS Cohort Study (MACS) used a frailty scale based on 4 self-reported deficits: weight loss, exhaustion, impaired physical activity, and difficulty walking [29]. One study used a single measure of unexpected weight loss to define frailty [40]. No published studies of frailty in people with HIV have used the cumulative deficit/frailty index approach, or scales based on clinical judgment.…”
Section: Measuring Frailty In Hiv-positive Individualsmentioning
confidence: 99%
“…For instance, analyses of the Multicenter AIDS Cohort Study (MACS) used a frailty scale based on 4 self-reported deficits: weight loss, exhaustion, impaired physical activity, and difficulty walking [29]. One study used a single measure of unexpected weight loss to define frailty [40]. No published studies of frailty in people with HIV have used the cumulative deficit/frailty index approach, or scales based on clinical judgment.…”
Section: Measuring Frailty In Hiv-positive Individualsmentioning
confidence: 99%
“…In the Kolkata study, majority of PLHIV belonged to stage 4. 12 In our study, the mean CD4 count was 308 + 224.8 cells/mm 3 . The mean CD4 count in the Greek study 9 was 303.86 + 236.22 cells/mm 3 .…”
Section: Discussionmentioning
confidence: 41%
“…Our findings are similar to the Kolkata and the Greek study. 12,17 In a study done in China, majority of elderly PLHIV were females. 25 Majority of elderly PLHIV in our study belonged to stage 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations